2010
DOI: 10.1002/mc.20697
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant DNA methylation of some tumor suppressor genes in lung cancers from workers with chromate exposure

Abstract: Our previous studies revealed a variety of genetic changes in lung cancers from chromate-exposed workers (chromate lung cancer). In the present study, we examined epigenetic changes in chromate lung cancers. Nested-methylation-specific PCR was employed in studying the methylation of CpG islands in the APC, MGMT, hMLH1 genes in 36 chromate lung cancers and 25 nonchromate lung cancers. Methylation in chromate lung cancers was detected at 86% for APC, 20% for MGMT, and 28% for hMLH1. Whereas, it occurred at lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 34 publications
1
77
1
Order By: Relevance
“…In the patients studied, MGMT methylation was less frequently observed in lung tumor tissues compared with other studies, which describe methylation frequencies of 10.0-77.8% (3,4,6,8,12,16,17). In contrast to the present study, the majority of other studies did not analyze normal tissue; therefore, statements concerning the use of MGMT methylation in the early detection of lung cancer by analyzing non-malignant samples cannot be reasonably made.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the patients studied, MGMT methylation was less frequently observed in lung tumor tissues compared with other studies, which describe methylation frequencies of 10.0-77.8% (3,4,6,8,12,16,17). In contrast to the present study, the majority of other studies did not analyze normal tissue; therefore, statements concerning the use of MGMT methylation in the early detection of lung cancer by analyzing non-malignant samples cannot be reasonably made.…”
Section: Discussioncontrasting
confidence: 99%
“…These six genes were chosen as they all appear to be relevant in tumor development and progression. The inactivation and, therefore, loss of expression of MGMT and RASSF1A in lung cancer has been described previously (3)(4)(5)(6)8,(12)(13)(14)(15)(16)(17). The reduced expression of RASAL1 was observed in several malignant tumors, including brain, head and neck, bladder, breast, colorectal, hepatocellular and thyroid carcinoma (18)(19)(20)(21), and appears to be associated with neoplastic progression (19).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Klein et al (2002) reported for the first time that potassium chromate, a carcinogen, causes aberrant DNA methylation and silences a reported gene in a mammalian cell line. Ali et al (2011) found higher rates of aberrant methylation in the promoters of three tumor-suppressor genes, APC (adenomatosis polyposis coli), MGMT (O 6 -methylguanine-DNA methyltransferase), and hMLH1 in lung cancers of chromate workers as compared to non-chromate lung cancer controls (95% versus 52%), with concordant methylation of multiple loci observed in more chromate lung cancers than in nonchromate ones (48% versus 12%). Chromate was also linked to post-translational histone modifications.…”
Section: Epigenetics and Environment Exposurementioning
confidence: 93%
“…An interesting example is provided by hexavalent chromium, to which half a million workers in the United States and several million individuals worldwide are occupationally exposed (Ali et al, 2011). Until recently, chromium was thought to cause cancer only through its ability to damage DNA (Arita & Costa 2009).…”
Section: Epigenetics and Environment Exposurementioning
confidence: 99%